2011
DOI: 10.1007/s10658-011-9784-4
|View full text |Cite
|
Sign up to set email alerts
|

Fireblight (Erwinia amylovora) affects Mal d 1-related allergenicity in apple

Abstract: Fireblight infection of apple and pear trees

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This low-level expression could be part of systemic acquired resistance of plants to prevent a further attack by biotrophic pathogens [44]. These differences in PR-protein and allergen encoding gene expression between leaves and fruits as well as between young and major plants have already been shown for different apple cultivars infected with fireblight [19]. The authors showed an up-regulation of major apple allergen Mal d 1.01 transcripts in leaves from seedlings after fireblight infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This low-level expression could be part of systemic acquired resistance of plants to prevent a further attack by biotrophic pathogens [44]. These differences in PR-protein and allergen encoding gene expression between leaves and fruits as well as between young and major plants have already been shown for different apple cultivars infected with fireblight [19]. The authors showed an up-regulation of major apple allergen Mal d 1.01 transcripts in leaves from seedlings after fireblight infection.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, PR-proteins show high homologies to allergens and allergenic activity could be confirmed in many PR-protein families [17], [18]. For example, in apple an infection of young leaves from seedlings by fireblight, a bacterial disease, provoked an increase in the PR-protein and allergen Mal d 1.01 encoding gene [19].…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the two up-regulated proteins (spots 11 and 13) were annotated as the same protein, s-adenosylmethionine synthetase (SAMS), which serves as a precursor in polyamine biosynthesis [44]. In addition, three proteins were identified as the same heat-shock protein (spots 1–2 and 37), which is usually involved in the stress response.…”
Section: Resultsmentioning
confidence: 99%
“…The largest group contained proteins related to defence response, including 2 up-regulated proteins ( Fig 3 , spots 11 and 13) and 13 down-regulated proteins ( Fig 3 , spots 1–2, 10, 15, 19, 28, 31–32, and 36–40). Interestingly, the two up-regulated proteins (spots 11 and 13) were annotated as the same protein, s-adenosylmethionine synthetase (SAMS), which serves as a precursor in polyamine biosynthesis [ 44 ]. In addition, three proteins were identified as the same heat-shock protein (spots 1–2 and 37), which is usually involved in the stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, ethylene associated to tissue wounding provoked an increase of the allergenic potency of turnip by inducing the expression of a prohevein [18]. Another example is given by the work of Mayer et al [19], who demonstrated the increase of Mal d 1 gene transcription and protein accumulation after infection by Erwinia amylovora . In contrast, a recent publication [20] showed that the infection of tomato by Pepino mosaic virus, despite inducing the overexpression of specific allergenic proteins, did not lead to a parallel increase of the allergenic potency of the fruit, analyzed by basophil activation test.…”
Section: Discussionmentioning
confidence: 99%